Association of radiation risk in the second and third generations with polymorphisms in the genes CYP1A1, CYP2E1, GSTP1 and changes in the thyroid - Meruyert Massabayeva; Nailya Chaizhunusova; Nurlan Aukenov; Tolkyn Bulegenov; Bakytbek Apsalikov; Aigerim Shapihanova; Yersin Zhunussov (Molecular Medicine, 2019)
Abstract Background To study the association of radiation risk in the 2nd –3rd generations with polymorphisms in the genes CYP1A1, CYP2E1, GSTP1 and changes in the thyroid. Methods 5 polymorphic gene variants (rs1048943, rs4646421, rs2070676, rs3813867, rs1695) were studied in 399 people living in the East Kazakhstan region in this research. 248 people of the 2nd - 3rd generation lived in the territory with radiation exposure in Abai, Borodulikha areas, and 151 people the comparison group lived in Kurchum district without radiation exposure comparable in sex and age with control group. Results The results show that there is a significant association of rs1048943 in exposed and unexposed groups (p < 0.003), and the absence of association of rs4646421, rs2070676, rs3813867, rs1695 in the studied groups. The mean value of thyroxine in carriers of the AG + GG genotype of rs4646421 is significantly lower than in AA genotype carriers (p = 0.04); no significant changes were found in genotypes’ distribution with thyroid-stimulating hormone and anti-thyroid peroxidase indicators. Significant changes were in levels of anti-thyroid peroxidase between exposed and unexposed groups (p = 0.007). The thyroxine - thyroid-stimulating hormone levels were not significantly different in exposed and unexposed groups (p > 0.3). Conclusions This study demonstrated the association of rs1048943 polymorphism with living in the radiation zone in the 2nd and 3rd generations for the first time. Thyroxine levels decrease was identified in the 2nd and 3rd generation residents of the exposed area, as well as a significant increase of anti-thyroid peroxidase occurs in individuals of the 2nd and 3rd generation living in areas with radiation exposure.